Analysis of the chronotropic effect of acetylcholine on sinoatrial node cells. - Zhang, H; Holden, A; Noble, D; Boyett, MR (2002)
INTRODUCTION: The ionic basis underlying the negative chronotropic effect of acetylcholine (ACh) on sinoatrial (SA) node cells is unresolved and controversial. In the present study, mathematical modeling was used to address this issue. METHODS AND RESULTS: The known concentration-dependent effects of ACh on iK,ACh, iCa,L, and i(f) were introduced into models of rabbit central and peripheral SA node cells. In the central and peripheral models, 9 x 10(-8) and 14 x 10(-8) M ACh, respectively, caused a 50% decrease in pacemaking rate, whereas in rabbit SA node to approximately 7.4 x 10(-8) M ACh caused such a decrease. In the models, iK,ACh was primarily responsible for the decrease and actions of ACh on iCa,L or i(f) alone caused a negligible effect. Although the inhibition of i(f) did not directly contribute to the chronotropic effect, it was indirectly important, because it minimized the opposition by i(f ) to the decrease of rate caused by activation of iK,ACh. The central model was more sensitive to ACh than the peripheral model. CONCLUSION: The chronotropic effect of ACh is principally the result of activation of iK,ACh, and inhibition of iCa,L plays little or no role. Inhibition of i(f) and possible inhibition of ib,Na play an important facilitative role by reducing the ability of i(f) and ib,Na to curtail the chronotropic effect caused by activation of iK,ACh.